Impact of Covid-19 in Changing Lifestyle Notions of Green Consumers: A Case Study of Dhankuta Municipality (Dristikon: A Multidisciplinary Journal, 2024)
This study investigates the impact of COVID-19 on green consumer lifestyle choices in Dhankuta Municipality, Nepal, employing a mixed approach to understand global and local effects. Utilizing a theoretical framework encompassing Economic Theory, Planned Behavior Theory, and Ecological Modernization Theory, the research aims to uncover the true influence of COVID-19 on lifestyle notions and sustainable practices. The methodology involves stratified sampling to ensure diverse perspectives, with a sample size of 406 respondents aged 18 and above. Demographic findings reveal a nearly balanced gender distribution (60% male, 40% female), with a significant proportion (39.7%) in the 26-35 age group, indicating their crucial role in consumer decisions. Notably, 37.2% of respondents have experienced COVID-19 infection, providing insights into the pandemic's impact. Findings demonstrate a substantial positive correlation (r = 0.675, p < 0.01) between COVID-19 and willingness to pay for green products. Regression analysis reveals a significant relationship between the pandemic and changes in lifestyle notions, explaining 72.3% of the variance. These results underscore the need for sustained exploration of post-COVID green consumer behavior and inform strategies for policymakers and businesses in fostering sustainable consumption in Dhankuta Municipality, Nepal.